The Patriarchal Construction of the Female Captivity of Beauty Illustrated in Twentieth Century Costa Rican Stories - Sanabria León, Jorge (2023)
The objective of this analysis is to identify features of the ideal of beauty represented, as a model of feminine identity, in ten Costa Rican short stories written between the years 1900 and 2000. The ideal of beauty in Costa Rican literature presupposes that cultural creation reproduces patterns of sociocultural socialization. Ten Costa Rican short stories were analyzed to illustrate the representations of the ideal of beauty for women as referents of female socialization models in Costa Rican culture. The applied methodology is based on deep psychoanalytic hermeneutics, which allowed analysis at various levels of meaning, from the intrinsic game in the text-reader relationship, which articulates the function of images, to the symbolizations in the text as an agent of socialization that collects, transmits, and debates sociocultural constructions (Sanabria, 2007). The study highlights that the ideal of female beauty does not refer exclusively to the physical appearance, but rather encompasses and controls various areas of women's subjectivity. It is a set of social orders directed towards women that are not static, but rather continue to adapt historically to patriarchal mandates on the female sociocultural role, which implies psychosocial impositions for female subordination where beauty is imposed as a form of captivity.